Health as Social Justice: Reconstructing the Health Law Paradigm Through a Legal Political Philosophy Approach - Santoso, Aris Prio Agus; Mahyuvi, Tata (KnE Social Sciences, 2025)
The Indonesian health law system remains predominantly administrative and technocratic in nature, thereby falling short in ensuring social justice in the distribution of healthcare services, particularly for vulnerable groups such as indigenous communities in underdeveloped, remote, and outermost (3T) regions. This study aims to reconstruct the paradigm of health law in Indonesia through the lens of legal political philosophy in order to promote a more inclusive, participatory, and sustainable approach to healthcare delivery. Employing a qualitative descriptive method, this research utilizes literature review and content analysis to explore and reformulate the health law paradigm based on secondary data interpreted through legal political philosophy. The findings suggest that legal political philosophy plays a critical role in reshaping the health law paradigm by highlighting the interconnection between law, political power, and morality, as well as the state’s responsibility to uphold the right to health in a fair and inclusive manner. This reconstruction must be grounded in principles of justice, transparency, public participation, and ethical integration, transforming health law into a vehicle for social emancipation that strengthens deliberative democracy and substantive justice.